CRISPR/Cas9 guided genome and epigenome engineering and its therapeutic applications in immune mediated diseases - Singh D.; Hawkins R.; Lahesmaa R.; Tripathi S. (Elsevier Ltd, 2022)
Recent developments in the nucleic acid editing technologies have provided a powerful tool to precisely engineer the genome and epigenome for studying many aspects of immune cell differentiation and development as well as several immune mediated diseases (IMDs) including autoimmunity and cancer. Here, we discuss the recent technological achievements of the CRISPR (Clustered Regularly Interspaced Short Palindromic Repeats)-based RNA-guided genome and epigenome editing toolkit and provide an insight into how CRISPR/Cas9 (CRISPR Associated Protein 9) toolbox could be used to examine genetic and epigenetic mechanisms underlying IMDs. In addition, we will review the progress in CRISPR/Cas9-based genome-wide genome and epigenome screens in various cell types including immune cells. Finally, we will discuss the potential of CRISPR/Cas9 in defining the molecular function of disease associated SNPs overlapping gene regulatory elements.